Convolvulus scammonia Effect on Gene Expression of Candida tropicalis Biofilms - Mouna Akeel Hamed Al-Oebady; Wafaa Ayad Al-Nuaimy; Noor Sami Al-Lebawy (Novel Research in Microbiology Journal)
Convolvulus scammonia is a twining perennial plant with thick, fleshy roots, irregularly arrow-shaped leaves, and flowers resembling those of Convolvulus arvensis. The aim of this study was to determine the impact of C. scammonia on six genes expression (i.e., ACT1, BCR1, EFG1, AlS1, AlS3, and TEC1), known to be implicated in the development of Candida tropicalis biofilms, and define the minimum inhibitory concentration (MIC) of C. scammonia required for this purpose. The 2,3-bis(2-metoxy-4-nitro-5-sulphophenyl)-2H-tetrazolium-5-carboxanilide inner salt (XTT) assay was used to assess the anti-biofilm activity of C. scammonia in order to ascertain the formation of biofilms on C. tropicalis isolates obtained from thrush samples and evaluate the MIC of C. scammonia that inhibits the biofilms of Candida tropicalis during 24 and 48 h. Finally, the impact of C. scammonia on ACT1, AlS1, AlS3, BCR1, TEC1, and EFG1gene expression in C. tropicalis was examined using a real-time polymerase chain reaction (RT-PCR) and compared to the results obtained in the gene expression of the control C. tropicalis biofilms untreated with C. scammonia during 24 and 48 h. Through comparison, biofilms formation was found to decrease as C, scammonia concentration and time increased. Accordingly, the MIC of C. scammonia was 20 % w/v, and its minimum fungicidal - concentration (MFC) was 40 % (w/v) in biofilm-forming C. tropicalis. Additionally, gene expression level analysis revealed a decrease in ACT1, AlS1, AlS3, BCR1, EFG1, and TEC1 expression levels on treatment with C. scammonia during 24 and 48 h.